2016
DOI: 10.1530/ec-16-0021
|View full text |Cite
|
Sign up to set email alerts
|

Plasma acylated and plasma unacylated ghrelin: useful new biomarkers in patients with neuroendocrine tumors?

Abstract: To date, the value of fasting plasma acylated ghrelin (AG) and unacylated ghrelin (UAG) as potential novel biomarkers in patients with neuroendocrine tumors (NETs) is unknown. The aims of this study are to (i) compare fasting AG and UAG levels between nonobese, nondiabetic NET patients (N=28) and age- (±3 years) and sex-matched nonobese, nondiabetic controls (N=28); and (ii) study the relationship between AG, UAG, and AG/UAG ratios and biochemical (chromogranin-A (CgA) and neuron-specific enolase (NSE) levels)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The difference could be due to the different tumor types between our study (insulinoma only) and theirs [42]. The plasma levels of acylated ghrelin did not correlate with clinicopathological characteristics which is consistent with previous findings [44].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The difference could be due to the different tumor types between our study (insulinoma only) and theirs [42]. The plasma levels of acylated ghrelin did not correlate with clinicopathological characteristics which is consistent with previous findings [44].…”
Section: Discussionsupporting
confidence: 90%
“…These researchers suggested that it was worthwhile to test acylated ghrelin levels in patients with NETs [41,42]. A recent study on NETs compared fasting acylated ghrelin and unacylated ghrelin levels between NET patients and controls, showed that there was no significant difference between patients and controls in fasting acylated ghrelin but only three patients with PNETs were included and, obese patients and obese matched controls were excluded in this study [44].…”
Section: Discussionmentioning
confidence: 99%
“…This is considerably lower than levels that have been observed in healthy control subjects, measured using equivalent two-site sandwich assays and stabilized with AEBSF. Adrichem et al (40) found median plasma AG levels of 57.2 pg/mL (range, 10 to 273 pg/mL) and median plasma UAG levels of 64.9 pg/mL (range, 8 to 331 pg/mL) in 28 healthy control subjects, whereas Liu et al (53) reported AG levels ranging from 43 to 366 pg/mL in four healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…All patients gave their written informed consent, and the study was approved by the Medical Ethics Committee of Erasmus University MC, Rotterdam. (39,40).…”
Section: Methodsmentioning
confidence: 99%
“…In patients with metastatic disease, the levels of ghrelin were elevated, compared with the control group, in up to 85% of cases ( 157 ). A later study focusing on the active peripheral forms of ghrelin (acylated ghrelin; desacyl ghrelin; acylated ghrelin/desacyl ghrelin ratio) found no statistical difference between patients with NETs and the control group ( 158 ).…”
Section: Ghrelin and Gi Tract Tumorsmentioning
confidence: 93%